Mitochondrial, nuclear, and endosymbiotic diversity of two recently introduced populations of the invasive Bemisia tabaci MED species in La Réunion. Issue 1 (23rd June 2014) - Thierry, Magali; Bile, Audrey; Grondin, Martial; Reynaud, Bernard; Becker, Nathalie; Delatte, Hélène; Schonrogge, Karsten; Nash, David
Abstract The whitefly Bemisia tabaci is a worldwide pest considered to be a complex of cryptic species. Its identification is primarily based on mitochondrial COI sequences. Microsatellite markers can also be used to identify this species and to study its population structure. Moreover, B. tabaci species harbour quite specific endosymbiont communities that can constitute additional markers for identification. Previous studies have demonstrated the occurrence of two B. tabaci species on the island of La Réunion: the exotic MEAM1 and the indigenous IO. A recent field survey revealed unusually high densities of whiteflies in Saint Pierre, and this could reflect the introduction of a new B. tabaci species. To test the putative introduction of a new invasive species, B. tabaci individuals were collected at Saint Pierre and at six additional sites. Among these samples, analyses were conducted on mitochondrial COI, microsatellites, and endosymbiont communities. Based on the mitochondrial COI marker, we detected in Saint Pierre two subgroups (Eastern and Western) characteristic of the invasive MED species. This is the first time these subgroups have been found in La Réunion. The analysis of microsatellite data from the seven sites around the island showed that (i) the geographical distribution of MED seems confined to Saint Pierre, (ii) no hybrids were detected between MED individuals and the resident species, and (iii) the MED population, while exhibiting two mitochondrial haplotypes, has a homogenous nuclear genetic background. The two MED subgroups differing in their mitochondrial haplotype also specifically differed in their endosymbiotic diversity.